Ancepsone A, a new cheilanthane sesterterpene from Aleuritopteris anceps. (22nd June 2022) - Jiang, Tianju; Dai, Xiling; Gao, Ting; Wang, Lili; Yang, Fan; Zhang, Yu; Wang, Nina; Huang, Guozheng; Cao, Jianguo
Graphical abstract: Abstract: Ancepsone A, a new sesterterpene with 13, 19-epoxycheilanthane skeleton, i.e (17 Z )-13, 19-epoxycheilanth-1, 17-diene-2-ol-3-one (1 ), together with eight known natural products (2  ∼ 9 ) were isolated from Aleuritopteris anceps . The structure of the new compound was established by means of 1D and 2D NMR, MS, and single-crystal X-ray diffraction methods. All compounds were isolated from A. anceps for the first time. Ancepsone A and the isolated flavonoids can moderately inhibit the proliferation of cancer cells.